Students’ Perceptions towards Problems in Classroom Management Faced by Pre-Service Teachers during Teaching Internship Program - Almansuri, Rusyda Diina (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2025)
The pre-service teachers are inexperience teachers. The pre-service teachers often faced some problems in regulating the classroom. Considering that reason, the researcher conducts a survey to pre-service teachers to know the perceptions and problems toward classroom management during their teaching internship programs. This study discussed about the perception and problem toward classroom management during teaching internship programs. This study employed survey design by using questionnaire. The respondents were 100 students of the 8th semester of English Language Education Program of IAIN Kediri. They have taken internship program in various schools across Kediri and the surrounding areas in semester 7. There were 12 items of questions in the questionnaire responded by all 100 students. In analyzing the data, the researcher used Microsoft Excel version 2019. The result of this study shows that the pre-service teachers faced some problems in managing classroom. The result is divided based on 12 dimensions of classroom management, the participants mostly faced the problems in eight out of twelve domains, which are class size, students’ behavior, rowdy students, individual attention, discipline maintenance, non-native language, assignment submission, and motivating student. Yet, a few participants feel do not have difficulties when managing the classroom. If they found any problems, they could handle it with appropriate techniques such as team teaching, using new teaching techniques and visual-audio aids.